Context and time in brand image constructions. Issue 5 (5th August 2014) - Rindell, Anne; Iglesias, Oriol
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to further understanding of the roles that time and context play in consumers' evolving brand image construction processes over time. Design/methodology/approach – This exploratory, qualitative research is based on the analysis and interpretation of 164 online consumer narratives pertaining to the consumers' most memorable coffee moments. Findings – Consumers build images of a brand through both fleeting moments over time linked to special occasions and everyday moments in their lives over time. Understanding image construction processes thus must go beyond just physical (location) and psychological (social) circumstances. Activity processes ("When I am doing […]") also are central to this understanding. Research limitations/implications – Time and context emerge as key determinants of consumers' brand image processes and should hence be explicitly recognised in branding research. This study focuses only on brand admirers; because the study context refers to a business-to-consumer product, the focus is the product brand. Practical implications – Considering the key role of memorable past moments (time and context) in consumers' brand image construction processes, branding strategies should reflect systematic efforts to identify these moments. Such an approach can provide opportunities for companies to deepen their consumer understanding and achieve a favourable presence in consumer contexts during which brand images get constructed. Originality/value – This study identifies key dimensions of time and context and thus furthers understanding of these dimensions in relation to brand images.